PENGARUH KUALITAS LAYANAN DAN HARGA TIKET TERHADAP KEPUASAN PELANGGAN PENGGUNA JASA KERETA API KALIGUNG MAS KELAS EKSEKUTIF PADA PT. KAI DAOP 4 SEMARANG - Duana Pratiwi, Ade; Sutopo, Sutopo (Diponegoro Journal of Management, 2012)
This research is aimed to analyze the effect of service quality and ticket price toward Executive Class user satisfaction of KA Kaligung Mas services. This study executive class of Kaligung Mas train as the object because it is the only one executive class train for Semarang-Tegal destination. This study was conducted using questionnaires toward 100 service users of Executive class of KA Kaligung Mas for the 4th Operational Zone, Semarang, as the respondents. The sampling used is purposive sampling. Then, the data is analyzed by quantitative and qualitative analysis. Quantitative analysis includes validity and reliability test, classical assumption test, multiple regression analysis, Goodness of Fit test through regression coefficient (R2), F test and t test. Qualitative analysis is the interpretation of the data obtained in this research and the explanations of the data processing result. The data analyzing by validity and reliability test and classic assumptions test were processed to produce a regression equation as follows: Y = 0,448 X1 + 0,304 X2. In where, the customer satisfaction variable was symbolized with Y, quality of service with X1, and the price variable with X2. Hypothesis testing used t-test showed that the two independent variables partially have a significant effect on customer satisfaction. From the F test could be seen that the two independent variables simultaneously have an effect on customer satisfaction. 0,411 of Adjusted R Square showed that 41,1 percent customer satisfaction variables can be explained by the two independent variables in the regression equation. While the 58,9 percent, is explained by other variables out of the two variables used in this study.